Handbuch Europäische Sprachkritik Online Standardisierung und Sprachkritik - Felder, Ekkehard; Jacob, Katharina; Schwinn, Horst; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Henning; Radtke, Edgar (Handbuch Europäische Sprachkritik Online, 2018)
This second volume of the "Online Handbook of Language Criticism - A European Perspective" focuses on the processes of standardisation in German, English, French, Italian, and Croatian and investigates them in the context of language criticism, comparing different aspects of standardisation and authorities involved. It highlights diachronic aspects relating to the shaping of norms for written and spoken language as well as synchronic aspects, such as the development of pluricentric standards and issues of orthography and codification.